Adverse Childhood Experiences, Trauma Symptoms, Mindfulness, and Intimate Partner Violence: Therapeutic Implications for Marginalized Men. Issue 4 (5th March 2020) - Voith, Laura A.; Russell, Katie; Lee, Hyunjune; Anderson, RaeAnn E.
Abstract : Adverse childhood experiences (ACEs) and trauma symptoms have been linked with intimate partner violence (IPV) perpetration and victimization among men, yet the field lacks depth in several key areas hampering progress toward violence intervention. Specifically, posttraumatic stress disorder (PTSD) dominates the field's scope of trauma symptoms under study, limiting understanding of other manifestations of trauma especially among men. Furthermore, most research focuses exclusively on men's physical IPV perpetration and rarely focuses on other types of IPV, severity of violence, or men's victimization. Also, few studies examine potential protective factors grounded in the ACE framework, such as mindfulness, among clinical populations. Finally, most research has not focused on men of color, despite some racial/ethnic minority groups disproportionate rates of IPV exposure. Therefore, the relationships between IPV frequency and severity (psychological, physical, injury) and ACEs, PTSD, trauma symptomology (separate from PTSD), and mindfulness self‐efficacy were examined in a sample of 67 predominantly low‐income men of color in a batterer intervention program. More than half of the sample (51.5%) reported exposure to four or more ACEs, and 31.1% met the clinical cutoff for a probable PTSD diagnosis. Higher ACE scores predicted increased rates for nearly all types of self‐reported IPV perpetration and victimization. PTSD symptoms and complex trauma symptom severity together explained between 13% and 40% of IPV outcomes, and each was uniquely associated with certain types of self‐reported IPV victimization and perpetration frequency and severity. Mindfulness self‐efficacy was associated with decreased self‐report psychological IPV perpetration and victimization frequency and severity. Clinical implications relevant to marginalized men are reviewed, including screening, training, and potential therapeutic interventions. Resumen: Las experiencias adversas en la infancia (EAI) y los síntomas de trauma se han asociado con la perpetración de violencia de pareja y la victimización entre los hombres, sin embargo, el ámbito carece de profundidad en varias áreas clave que obstaculizan el avance hacia la intervención en la violencia. Específicamente, el trastorno por estrés postraumático (TEPT) domina el alcance de los síntomas de trauma del ámbito estudiado, lo cual limita la comprensión de otras manifestaciones de trauma, especialmente entre los hombres. Además, la mayoría de las investigaciones se centran exclusivamente en la perpetración de violencia física de pareja por parte de los hombres y rara vez se centra en otros tipos de violencia de pareja, en la gravedad de la violencia o en la victimización de los hombres. Además, pocos estudios analizan posibles factores protectores basados en el marco de las EAI, como la conciencia plena, entre las poblaciones clínicas. Finalmente, la mayoría de las investigaciones no se han centrado en los hombres de color, a pesar de algunos índices desmesurados de exposición a la violencia de pareja de grupos raciales/étnicos minoritarios. Por lo tanto, se analizó la relación entre la frecuencia de la violencia de pareja y la gravedad de esta (psicológica, física, lesiones) y las EAI, el TEPT, la sintomatología del trauma (aparte del TEPT), y la autoeficacia de la conciencia plena en una muestra de 67 hombres de color, predominantemente de bajos recursos, en un programa de intervención para golpeadores. Más de la mitad de la muestra (el 51, 5 %) informó exposición a cuatro o más EAI y el 31, 1 % alcanzó el umbral de decisión clínica para un diagnóstico probable de TEPT. Los puntajes más altos de EAI predijeron índices mayores de casi todos los tipos de perpetración de violencia de pareja y victimización autoinformadas. Los síntomas de TEPT y la gravedad de los síntomas de trauma complejo explicaron juntos entre el 13 % y el 40 % de los resultados de la violencia de pareja, y cada uno estuvo asociado exclusivamente con ciertos tipos de gravedad y frecuencia de la victimización y la perpetración de violencia de pareja autoinformadas. La autoeficacia de la conciencia plena estuvo asociada con una menor victimización y perpetración autoinformadas de la frecuencia y la gravedad de la violencia psicológica de pareja. Se revisan las implicancias clínicas relevantes para los hombres marginados, entre ellas, la evaluación, la capacitación y las posibles intervenciones terapéuticas. 摘要: 研究认为男子童年时期的不良经历（ACEs）和精神创伤症状与其IPV犯罪行为（亲密伴侣暴力）和被虐待经历是有关联的，但是针对暴力实施干预措施时起到阻碍作用的几个重要方面尚未得到深入研究。具体而言，创伤后应激障碍（PTSD）主导了该领域所研究的创伤症状的范围，限制了研究者对创伤的其他表现形式的理解，尤其是男子的创伤。此外，大多数研究只侧重于男性在身体方面的 IPV 犯罪行为，很少聚焦于诸如其他类型的 IPV行为、暴力严重程度或男性受迫害等研究方向。另外，很少有研究关注基于ACE框架的可能性保护因素，例如临床人群的觉知行为。最后，大多数研究的对象还尚未关注到有色人种，尽管一些种族/少数民族群体对IPV的接触率比较高。基于以上原因，本研究调查了IPV的发生频率和严重程度（心理、身体、伤害）与ACES、PTSD、创伤症状学（与PTSD区别开来），还有觉知的自我效能之间的相互关联。样本来自67个有色人种的男子，他们大多数属于低收入，正在参与虐妻行为干预计划。超过一半的样本（51.5%）报告曾经经历过四次或四次以上 ACEs ，有31.1%的被研究对象 满足疑似 PTSD 病人诊断标准。较高的 ACE 分数预测了几乎所有类型的自报 的较高IPV 犯罪率和较高的受害比例。PTSD 症状和复杂性创伤症状的严重程度综合在一起解释了 13% 到 40% 的 IPV 结果，而且每种结果都与某些类型的自报 的IPV 受害和暴力实施频率和严重程度有独特的关联性。觉知的自我效能与犯罪行为和受害经历发生减少，自我报告的心理方面的IPV频率和严重程度呈减少趋势有关。本研究综述了针对非主流的边缘化男性群体所采取的相关临床措施，包括筛查、培训和可能采用的治疗性干预方法。